Phylogenetic relationship and virulence composition of Escherichia coli O26:H11 cattle and human strain collections in Scotland; 2002–2020 - Hoyle, Deborah V.; Wee, Bryan A.; Macleod, Kareen; Chase-Topping, Margo E.; Bease, Andrew G.; Tongue, Sue C.; Gally, David L.; Delannoy, Sabine; Fach, Patrick; Pearce, Michael C.; Gunn, George J.; Holmes, Anne; et al. (Frontiers in Microbiology, 2023)
O26 is the commonest non-O157 Shiga toxin (stx)-producing Escherichia coli serogroup reported in human infections worldwide. Ruminants, particularly cattle, are the primary reservoir source for human infection. In this study we compared whole genomes and virulence profiles of O26:H11 strains (n=99) isolated from Scottish cattle with strains from human infections (n=96) held by the Scottish Escherichia coli O157/ STEC Reference Laboratory, isolated between 2002-2020. Bovine strains were from two national cross-sectional cattle surveys conducted between 2002-2004 and 2014-2015. A Maximum Likelihood phylogeny was constructed from a core genome alignment with the O26:H11 11368 reference genome. Genomes were screened against a panel of 2710 virulence genes using the Virulence Finder Database.All stx-positive bovine O26:H11 strains belonged to the ST21 lineage and were grouped into three main clades. Bovine and human source strains were interspersed and stx subtype was relatively clade specific. Highly pathogenic stx2a-only ST21 strains were identified in two herds sampled in the second cattle survey and human clinical infections from 2010 onwards. The closest pairwise distance was 9 single nucleotide polymorphisms (SNPs) between Scottish bovine and human strains and 69 SNPs between the two cattle surveys. Bovine O26:H11 were compared to public EnteroBase ST29 complex genomes and found to have greatest commonality with O26:H11 strains from the rest of the UK, followed by France, Italy and Belgium.Virulence profiles of stx-positive bovine and human strains were similar, but more conserved for the stx2a subtype. O26:H11 stx-negative ST29 (n=17) and ST396 strains (n=5) were isolated from 19 cattle herds; all were eae-positive and ten of these herds yielded strains positive for ehxA, espK and Z2098, gene markers suggestive of enterohaemorrhagic potential. There was a significant association (p<0.001) between nucleotide sequence percent identity and stx status for the bacteriophage insertion site genes yecE for stx2, and yehV for stx1. Acquired antimicrobial resistance genes were identified in silico in 12.1% of bovine and 17.7% of human O26:H11 strains, with sul2, tet, aph(3") and aph(6") being most common. This study describes the diversity among Scottish bovine O26:H11 strains and investigates their relationship to human STEC infections.